The complete mitochondrial genome sequence of Astyanax paranae (Teleostei: characiformes) - Silva, Duilio M. Z. de A. [UNESP]; Utsunomia, Ricardo [UNESP]; Ruiz-Ruano, Francisco J.; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Taylor & Francis Ltd, 2016)
Complete mitochondrial genome of the characiform fish Astyanax paranae was characterized in the present study. The whole mitogenome was 16,707 bp long and consisted of 13 protein-coding genes, 22 tRNAs, 2 rRNAs genes, a control region and origin of light-strand replication. The gene order is similar to those of the congeneric blind cavefish A. mexicanus. The nucleotide content of A. paranae mitogenome was 29.5% for A, 27.6% for T, 15.8% for G, 27.1% for C. Nucleotide identity between A. paranae and A. mexicanus across all the 37 genic regions ranged from 74.9% (ND2) to 90.3% (COX3).
Keywords: Characidae; mitochondrial DNA; mtDNA; next generation sequencing